Parents’ Coping Mechanism in Conquering Challenges towards Distribution and Retrieval of Modules - Pentang, Jupeth; Carbonilla, Mary Joy B.; Kadusale, Geraldine B.; Lucero, Rhea G.; Pungyan, May Rose D. (Future Science / FSH-PH Publications, 2022)
This research determined the challenges encountered by the parents from three schools in Palawan, Philippines, and their applied coping mechanisms concerning modular distance learning. The inquiry employed a mixed-method research design with 100 randomly sampled participants for the quantitative part and 12 purposively chosen participants for the qualitative component. Results revealed that the main challenge encountered by parents in distributing and retrieving modules is having no time to teach children at home. Nonetheless, the parents could cope with their challenges in supporting their child’s education. The result aims to promote awareness to the concerned parents on how they are going to manage challenges when it comes to the distribution and retrieval of modules, to have a positive outlook and mindset, to contribute to the smooth flow with regards to the distribution and retrieval of modules for the next school year.